Specifics of the Body Image of Adolescents with Scoliosis: A Case of Being Labeled as ‘A Scoliotic’ - Deputatov, Vladyslav; Velykodna, Mariana (International Journal of Child Health and Nutrition, 2021)
The body image is to be reconstructed during adolescence, which is more difficult in the case of somatic illness and social stigma. This research aimed to study adolescents' body image with scoliosis, students of a special educational institution in Ukraine socially identified with stigma as 'a school for scoliotics'. The participants (n=104) of the research were adolescents (13-15 years old) with scoliosis from the institution mentioned above (n=52, 24 males, 28 females) and adolescents without scoliosis from the same city (n=52, 24 males, 28 females). Two methods were used to collect the data: (1) Self-portraits; (2) Dembo-Rubinstein Self-Assessment Scale. The adolescents with scoliosis and labeled as 'scoliotics' face additional obstructions in their psychic body development compared to their peers. For instance, they tend to overinvest in the desired image of a healthy body and do not feel able to get it. We found the markers of four different ways to cope with the situation by the adolescents with scoliosis: (a) identification as 'a scoliotic' instead of hope to be cured soon; (b) psychological distancing from the others to preserve the desire of a more attractive body image; (c) repression or denial of the body parts which could relate to scoliosis; (d) infantilization, aimed to slow down the discovery of their maturing corporeality. Consequently, adolescents with scoliosis affected by stigma experience the gap or conflict between their current, desired and perceived realistic body image.